Colloid mobilization in an undisturbed sediment core under semiarid recharge rates. Issue 8 (19th August 2013) - Liu, Ziru; Flury, Markus; Harsh, James B.; Mathison, Jon B.; Vogs, Carolina
<x xml:space="preserve">Abstract</x> [1] The semiarid US Department of Energy Hanford site has a deep vadose zone with low recharge rates. Contaminants originating from nuclear waste processing are expected to move slowly through the vadose zone. The movement of certain contaminants can be facilitated by colloids. We hypothesized that the low recharge rates and low water contents in semiarid regions, however, tend to inhibit movement of colloidal particles, thereby reducing the risk for colloid‐facilitated contaminant transport. The goal of this study was to investigate whether in situ natural colloids can be mobilized and transported in undisturbed, deep vadose zone sediments at the Hanford site under typical, semiarid recharge rates. We sampled an undisturbed sediment core (i.d. 50 cm, 59.5 cm height) from a depth of 17 m below ground at the Hanford 200 Area. The core was set up as a laboratory lysimeter and exposed to an infiltration rate of 18 mm/yr by applying simulated pore water onto the surface. Particle concentrations were quantified in the column outflow, and selected samples were examined microscopically and for elemental composition (transmission electron microscopy and energy dispersive X‐ray). Measured water contents and potentials were used to calibrate a numerical model (HYDRUS‐1D), which was then applied to simulate colloid mobilization from the sediment core. During 5.3 years of monitoring, natural colloids like silicates, aluminosilicates, and Fe‐oxides were observed in the core outflow, indicating the continuous mobilization of in situ colloids. The total amount of particles mobilized during 5.3 years corresponded to 1.1% of the total dispersible colloids inside the core. Comparison of the amounts of colloids released with weathering rates suggests that mineral weathering can be a major source of the mobilized colloids. The fitted colloid release rate coefficient was 6 to 7 orders of magnitude smaller than coefficients reported from previous studies, where disturbed Hanford sediments and higher flow rates were used. Our findings demonstrate that even under low recharge rates and water contents typical for semiarid, deep vadose zone sediments, particles can continuously be mobilized, although the total mass of particles is low.